Growth in utero, adult blood pressure, and arterial compliance. Issue 2 (February 1995) - Martyn, C. N.; Barker, D. J.; Jespersen, S.; Greenwald, S.; Osmond, C.; Berry, C.
Abstract : OBJECTIVES–To examine the relation between disproportionate fetal growth and adult blood pressure and to investigate whether arterial compliance in adult life is related to early development. DESIGN–A follow up study of a group of men and women whose birth weights and other measurements of body size had been recorded at birth. SETTING–Home and outpatient study. SUBJECTS–337 men and women born in the Jessop Hospital, Sheffield, between 1939 and 1940. MAIN OUTCOME–Adult systolic and diastolic blood pressures and arterial compliance as measured by pulse wave velocity in two arterial segments. RESULTS–Both systolic and diastolic blood pressures were higher in people whose birth weight was low, who were short or who had small abdominal or head circumferences at birth. Systolic blood pressure decreased by 2.7 mm Hg (95% CI 0.8 to 4.6) for each pound (454 g) gain in birth weight and by 3.4 mm Hg (95% CI 1.4 to 5.4) for each inch (2.54 cm) increase in crown-heel length. Diastolic pressure fell by 1.9 mm Hg (95% CI 0.9 to 2.9) for each pound (454 g) gain in birth weight and by 2.4 mm Hg (95% CI 1.4 to 3.5) for each inch (2.54 cm) increase in length. Systolic blood pressure was also higher in individuals whose mother's intercristal pelvic diameter was small or whose mother's blood pressure had been raised during pregnancy but these effects were statistically independent of the effects of low birth weight and other measurements that indicate fetal growth retardation. Arterial compliance was lower in those who had been small at birth. CONCLUSION–Impairment of fetal growth is associated with raised blood pressure in adult life and decreased compliance in the conduit arteries of the trunk and legs.